Mechanisms by which statins protect endothelial cells from radiation-induced injury in the carotid artery - Karima Ait-Aissa; Karima Ait-Aissa; Linette N. Leng; Nathanial R. Lindsey; Xutong Guo; Denise Juhr; Olha M. Koval; Isabella M. Grumbach; Isabella M. Grumbach; Isabella M. Grumbach (Frontiers in Cardiovascular Medicine)
BackgroundThe incidental use of statins during radiation therapy has been associated with a reduced long-term risk of developing atherosclerotic cardiovascular disease. However, the mechanisms by which statins protect the vasculature from irradiation injury remain poorly understood.ObjectivesIdentify the mechanisms by which the hydrophilic and lipophilic statins pravastatin and atorvastatin preserve endothelial function after irradiation.MethodsCultured human coronary and umbilical vein endothelial cells irradiated with 4 Gy and mice subjected to 12 Gy head-and-neck irradiation were pretreated with statins and tested for endothelial dysfunction, nitric oxide production, oxidative stress, and various mitochondrial phenotypes at 24 and 240 h after irradiation.ResultsBoth pravastatin (hydrophilic) and atorvastatin (lipophilic) were sufficient to prevent the loss of endothelium-dependent relaxation of arteries after head-and-neck irradiation, preserve the production of nitric oxide by endothelial cells, and suppress the cytosolic reactive oxidative stress associated with irradiation. However, only pravastatin inhibited irradiation-induced production of mitochondrial superoxide; damage to the mitochondrial DNA; loss of electron transport chain activity; and expression of inflammatory markers.ConclusionsOur findings reveal some mechanistic underpinnings of the vasoprotective effects of statins after irradiation. Whereas both pravastatin and atorvastatin can shield from endothelial dysfunction after irradiation, pravastatin additionally suppresses mitochondrial injury and inflammatory responses involving mitochondria. Clinical follow-up studies will be necessary to determine whether hydrophilic statins are more effective than their lipophilic counterparts in reducing the risk of cardiovascular disease in patients undergoing radiation therapy.